ChemInform Abstract: Rapid, Regioconvergent, Solvent‐Free Alkene Hydrosilylation with a Cobalt Catalyst. Issue 13 (March 2016) - Chen, Chi; Hecht, Maxwell B.; Kavara, Aydin; Brennessel, William W.; Mercado, Brandon Q.; Weix, Daniel J.; Holland, Patrick L.
Abstract: The utility of β‐diketiminate cobalt(I)‐arene complexes as catalyst for the hydrosilylation of terminal alkenes with phenylsilane and triethoxysilane is demonstrated.